MEASURING THE RELATIVE IMPORTANCE OF APPLYING ENGINEERING SOLUTIONS TO URBAN TRAFFIC INTERSECTIONS: A PLANNING PERSPECTIVE - Firas ALRAWI (Scientific Journal of Silesian University of Technology. Series Transport)
This research is an attempt to compare engineering solutions for traffic intersections from a planning viewpoint. In this research, various solutions have been discussed for traffic intersections (traffic light, roundabout, underpass and overpass). The research highlighted the importance of each of these solutions in urban environments and clarified all variables related to the pros, cons, costs, capacity and environmental compatibility of each of these solutions with the surrounding urban environment. Weights were developed for all these variables, then correlation was determined using the linear regression method. The analysis of statistical results shows that the creation of underpasses often achieves most of the designated goals when compared to other solutions, despite some technical difficulties and high construction costs.